Isolation and characterization of three novel lytic phages against K54 serotype carbapenem-resistant hypervirulent Klebsiella pneumoniae - Fang, Chengju; Dai, Xiaoyi; Xiang, Li; Qiu, Yichuan; Yin, Ming; Fu, Yu; Li, Ying; Zhang, Luhua (Frontiers in Cellular and Infection Microbiology, 2023)
The emergence of carbapenem-resistant hypervirulent Klebsiella pneumoniae (CR-hvKP) has driven us to explore alternative treatments for the limitation of antimicrobial agents. Lytic phages are considered a promising alternative treatment for CR-hvKP infection. In this study, we reported three novel lytic phages, vB_KpnA_SCNJ1-Z, vB_KpnS_SCNJ1-C, and vB_KpnM_SCNJ1-Y, against a CR-hvKP strain SCNJ1, and they possess genomes of double-stranded DNA with a size of 43,428 bp, 46,039 bp, and 50,360 bp, respectively. Phylogenetic analysis demonstrated that vB_KpnA_SCNJ1-Z belongs to the family Autographiviridae within the class Caudoviricetes, while vB_KpnS_SCNJ1-C and vB_KpnM_SCNJ1-Y are unclassified Caudoviricetes. The phages showed a narrow host range only lysing 1 of 50 tested clinical bacterial strains. The one-step growth curves and stability results showed that the phages displayed relatively short latency periods, with broad pH (pH 3-14) and thermal stabilities (20–60°C). The phages showed significant inhibition of the biofilm formation by SCNJ1 and strong antibacterial activity in vitro. In the mouse model, we demonstrated that administration of a single phage or phage cocktail significantly reduced bacteria loads in the lung, liver, and spleen, and effectively rescued mice from the infection of the SCNJ1 strain, with a survival rate of 70-80%. These findings suggested the three phages have great potential as an alternative therapy with favorable stability and strong antibacterial activity both in vivo and in vitro for the treatment of CR-hvKP infection.